A randomized, single-ascending-dose, ivermectin-controlled, double-blind study of moxidectin in Onchocerca volvulus infection. - Kwablah Awadzi; Nicholas O Opoku; Simon K Attah; Janis Lazdins-Helds; Annette C Kuesel (Public Library of Science (PLoS), 2014)
BACKGROUND:Control of onchocerciasis as a public health problem in Africa relies on annual mass ivermectin distribution. New tools are needed to achieve elimination of infection. This study determined in a small number of Onchocerca volvulus infected individuals whether moxidectin, a veterinary anthelminthic, is safe enough to administer it in a future large study to further characterize moxidectin's safety and efficacy. Effects on the parasite were also assessed. METHODOLOGY/PRINCIPAL FINDINGS:Men and women from a forest area in South-eastern Ghana without ivermectin mass distribution received a single oral dose of 2 mg (N = 44), 4 mg (N = 45) or 8 mg (N = 38) moxidectin or 150 µg/kg ivermectin (N = 45) with 18 months follow up. All ivermectin and 97%-100% of moxidectin treated participants had Mazzotti reactions. Statistically significantly higher percentages of participants treated with 8 mg moxidectin than participants treated with ivermectin experienced pruritus (87% vs. 56%), rash (63% vs. 42%), increased pulse rate (61% vs. 36%) and decreased mean arterial pressure upon 2 minutes standing still after ≥5 minutes supine relative to pre-treatment (61% vs. 27%). These reactions resolved without treatment. In the 8 mg moxidectin and ivermectin arms, the mean±SD number of microfilariae/mg skin were 22.9±21.1 and 21.2±16.4 pre-treatment and 0.0±0.0 and 1.1±4.2 at nadir reached 1 and 3 months after treatment, respectively. At 6 months, values were 0.0±0.0 and 1.6±4.5, at 12 months 0.4±0.9 and 3.4±4.4 and at 18 months 1.8±3.3 and 4.0±4.8, respectively, in the 8 mg moxidectin and ivermectin arm. The reduction from pre-treatment values was significantly higher after 8 mg moxidectin than after ivermectin treatment throughout follow up (p<0.01). CONCLUSIONS/SIGNIFICANCE:The 8 mg dose of moxidectin was safe enough to initiate the large study. Provided its results confirm those from this study, availability of moxidectin to control programmes could help them achieve onchocerciasis elimination objectives. TRIAL REGISTRATION:ClinicalTrials.gov NCT00300768.